Microstructure and corrosion resistance of inorganic-organic (ZrO2-PMMA) hybrid coating on stainless steel - Messaddeq, S. H.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Guastaldi, Antonio Carlos [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 1999)
Zirconia-polymethylmetacrylate hybrids prepared by a sol-gel method were deposited by dip-coating on stainless steel to improve the resistance against wet corrosion. The effect of the concentration of polymethylmetacrylate and the number of coating applications on the microstructure and corrosion performance of coated samples was investigated. The microstructural properties of samples was analyzed by scanning electron and atomic force microscopy, adhesion tests and profilemeter measurements. The electrochemical corrosion was evaluated through potentiodynamic polarization curves at room temperature. Results show that the sample prepared with 17 vol.% of polymethylmethacrylate has a maximum corrosion resistance, smaller roughness, are hermetic and adherent to the substrate. This film increases the life time of the stainless steel by a factor 30. (C) 1999 Elsevier B.V. B.V. All rights reserved.